Gastrite eosinofílica - Relato de caso - Bruno Carminatti da Silva; Jaqueline Cavalcanti de Albuquerque Ratier; Mônica Lisboa Chang Wayhs; Camila Marques de Valois Lanzarin; Renata Meirelles Gaspar Coelho Tomazzoni (Residência Pediátrica)
Eosinophilic gastritis is a rare condition characterized by a dense infiltration of eosinophils in the gastric mucosa. The suggested pathophysiological processes are multifactorial and involve mechanisms that lie between an immunoglobulin E-mediated response and a late T helper 2 response. The clinical presentation is variable and there is a strong association between allergic disorders and eosinophilic gastritis. In this report we describe the clinical and laboratory findings of eosinophilic gastritis in a 9-year-old boy treated with prednisolone and double-dose esomeprazole.